Beta‐band oscillations during passive listening to metronome sounds reflect improved timing representation after short‐term musical training in healthy older adults. (4th October 2017) - Fujioka, Takako; Ross, Bernhard
Abstract: Sub‐second time intervals in musical rhythms provide predictive cues about future events to performers and listeners through an internalized representation of timing. While the acuity of automatic, sub‐second timing as well as cognitively controlled, supra ‐second timing declines with ageing, musical experts are less affected. This study investigated the influence of piano training on temporal processing abilities in older adults using behavioural and neuronal correlates. We hypothesized that neuroplastic changes in beta networks, caused by training in sensorimotor coordination with timing processing, can be assessed even in the absence of movement. Behavioural performance of internal timing stability was assessed with synchronization–continuation finger‐tapping paradigms. Magnetoencephalography (MEG) was recorded from older adults before and after one month of one‐on‐one training. For neural measures of automatic timing processing, we focused on beta oscillations (13–30 Hz) during passive listening to metronome beats. Periodic beta‐band modulations in older adults before training were similar to previous findings in young listeners at a beat interval of 800 ms. After training, behavioural performance for continuation tapping was improved and accompanied by an increased range of beat‐induced beta modulation, compared to participants who did not receive training. Beta changes were observed in the caudate, auditory, sensorimotor and premotor cortices, parietal lobe, cerebellum and medial prefrontal cortex, suggesting that increased resources are involved in timing processing and goal‐oriented monitoring as well as reward‐based sensorimotor learning. Abstract : After one month of piano training, induced neuromagnetic beta oscillations in older adults exhibited an increased range of modulation during passive listening to metronome beats, accompanied by improved timekeeping ability. Beta changes involved the caudate, auditory, sensorimotor and premotor cortices, parietal lobe, cerebellum and medial prefrontal cortex, suggesting increased resources for timing processing and goal‐oriented monitoring as well as reward‐based sensorimotor learning.